Stereoselective synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine: observation of a substrate dependent diastereoselectivity reversal of an aldol reaction - Mondal, Pravat; N. P. Argade (Organic & Biomolecular Chemistry, 2016)
Starting from (-)-acetoxyglutarimide, the enantioselective multistep synthesis of (-)-desethyleburnamonine, (-)-vindeburnol and (-)-3-epitacamonine has been demonstrated via a common hydroxyl-lactam intermediate with very good overall yields. The acetoxy function from (-)-acetoxyglutarimide was initially used as a handle to induce enantioselectivity and then as a latent source of the ketone carbonyl group. Most importantly, substrate dependent reversal of the diastereoselectivity in ester aldol reactions of hexahydroindolo[2,3-a] quinolizinones has been reported.